Analyzing The Influential Factors of Sports Brands on Brand Equity - Zhang, Zhixian (Transactions on Economics, Business and Management Research, 2024)
For many years, marketing evaluation hazed on brand equity, and there has been an increasing academic interest in measuring brand equity through specific brand experiences. In this area, the sports industry continues to play a growing role, with most major brands participating in sports event marketing activities, including Decathlon. This study aims to explore the use of sports event marketing by the Decathlon Group and explain the effectiveness of this strategy on its brand equity through case analysis. The study reveals that brand association, brand loyalty, and brand value significantly influence consumer decision-making and overall brand equity. Decathlon's partnership with the Paris 2024 Olympic Games benefits its brand association, brand value, and brand loyalty, ultimately improving its overall brand equity from these three perspectives, as proven by examining the details of their marketing tactics and combining them with marketing theory. Additionally, specific suggestions are provided for areas where Decathlon may lack direction in their marketing efforts. These findings serve as a reference point for further investigation into comparing different marketing tactics from this perspective.